2021
DOI: 10.1101/2021.02.10.21251496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timely referral for advanced therapy in Parkinson’s disease. Development of a screening tool

Abstract: OBJECTIVES: To develop a screening tool for timely referral for advanced therapy (AT) in patients with Parkinson disease (PD), and to compare the newly-developed tool with the published 5-2-1 criteria. DESIGN: Cross-sectional, diagnostic, observational study and multivariable logistic regression analysis for item selection. SETTING: 8 hospitals in the Northern part of the Netherlands situated in the catchment area of a specialized movement disorder centre. PARTICIPANTS: 259 consecutive PD patients not yet … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Based on their findings, the authors constructed a three-factor screening tool based on LED, response fluctuations, and troublesome dyskinesias, to screen for patients eligible for DAT referral. This study reported a sensitivity and a specificity of 88 and 98% compared with 94 and 73%, respectively, for the 5-2-1 criteria [18]. The authors note that their tool corroborates the concepts of the 5-2-1 criteria, and the study appears to confirm the validity of the overall approach.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Based on their findings, the authors constructed a three-factor screening tool based on LED, response fluctuations, and troublesome dyskinesias, to screen for patients eligible for DAT referral. This study reported a sensitivity and a specificity of 88 and 98% compared with 94 and 73%, respectively, for the 5-2-1 criteria [18]. The authors note that their tool corroborates the concepts of the 5-2-1 criteria, and the study appears to confirm the validity of the overall approach.…”
Section: Discussionsupporting
confidence: 60%
“…In a similar way anticipated for the 5-2-1 criteria, MANAGE-PD section 1 groups patients into controlled or inadequately controlled on current therapy. A recently-reported study compared the 5-2-1 criteria to a newly developed screening tool designed to predict eligibility for referral for DAT evaluation [18]. In this study, a panel of experts assessed 259 consecutive DAT-naive PD patients, of whom 17 were considered eligible for DAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations